Bioprocessing of differentiated plant in vitro systems. Issue 1 (4th December 2012) - Steingroewer, Juliane; Bley, Thomas; Georgiev, Vasil; Ivanov, Ivan; Lenk, Felix; Marchev, Andrey; Pavlov, Atanas
<x xml:space="preserve">Abstract</x> Plant cells contain a wide range of interesting secondary metabolites, which are used as natural pigments and flavoring agents in foods and cosmetics as well as phyto‐pharmaceutical products. However, conventional industrial extraction from whole plants or parts of them is limited due to environmental and geographical issues. The production of secondary metabolites from in vitro cultures can be considered as alternative to classical technologies and allows a year‐round cultivation in the bioreactor under optimal conditions with constant high‐level quality and quantity. Compared to plant cell suspensions, differentiated plant in vitro systems offer the advantage that they are genetically stable. Moreover, the separation of the biomass from culture medium after fermentation is much easier. Nevertheless, several investigations in the literature described that differentiated plant in vitro systems are instable concerning the yield of the target metabolites, especially in submerged cultivations. Other major problems are associated with the challenges of cultivation conditions and bioreactor design as well as upscaling of the process. This article reviews bioreactor designs for cultivation of differentiated plant in vitro systems, secondary metabolite production in different bioreactor systems as well as aspects of process control, management, and modeling and gives perspectives for future cultivation methods.